(untitled) (Confluenţe Bibliologice, 2019)
The author makes the reader familiar with the article of Răzvan Theodorescu Romanian, researcher and academician ,who wrote about the life of the Romanian Maria/ Queen Maria, an aristocrat by deﬁning the Danubian and Carpathian people, leaving behind the memory of the lived life and the love for Romania, the earth with its joys and pains, the beautiful country living in her heart and whose way she has known.